Cluster of Angiostrongyliasis Cases Following Consumption of Raw Monitor Lizard in the Lao People’s Democratic Republic and Review of the Literature - Yang, Leeyounjera (Trop Med Infect Dis, 2021)
Angiostrongyliasis in humans causes a range of symptoms from mild headache and myalgia to neurological complications, coma and death. Infection is caused by the consumption of raw or undercooked intermediate or paratenic hosts infected with Angiostrongylus cantonensis or via contaminated vegetables or water. We describe a cluster of cases involved in the shared meal of wild raw monitor lizard in the Lao PDR. Seven males, aged 22–36 years, reported headaches, abdominal pain, arthralgia, myalgia, nausea/vomiting, diarrhea, neurological effects and loss of appetite. Five were admitted to hospital. The final diagnosis was made by clinical presentation and case history, and positive A. cantonensis PCR for two cases. All hospitalized patients recovered fully following supportive treatment. The remaining two individuals sought local home remedies and made full recovery. Whilst most published reports concern infections via consumption of molluscs, few detailed reports exist on infections that result from the consumption of reptiles and there exists little awareness in Lao PDR. This case cluster, which originates from a single meal, highlights the potential public health risk of the consumption of raw and wild-caught meat in Lao PDR and the Southeast Asia region. Without specific diagnostics, clinical history and the consideration of recent food consumption are important when evaluating patients.